2021
DOI: 10.1186/s40104-021-00556-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals the molecular mechanisms of rumen wall morphological and functional development induced by different solid diet introduction in a lamb model

Abstract: Background This study aimed to elucidate the molecular mechanisms of solid diet introduction initiating the cellular growth and maturation of rumen tissues and characterize the shared and unique biological processes upon different solid diet regimes. Methods Twenty-four Hu lambs were randomly allocated to three groups fed following diets: goat milk powder only (M, n = 8), goat milk powder + alfalfa hay (MH, n = 8), and goat milk powder + concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…The improvement of body size indices was slow in the milk phase, whereas it was remarkable in the MMSD phase. In addition, the weaning transition is an essential phase for the manipulation of rumen development using nutritional strategies, which can affect ruminant growth performance and health (Sun et al, 2021). The current study results confirmed the beneficial effects of solid feed to enhance the preweaning growth and overcome the weaning stress.…”
Section: Body Weight and Carcass Weightsupporting
confidence: 78%
See 3 more Smart Citations
“…The improvement of body size indices was slow in the milk phase, whereas it was remarkable in the MMSD phase. In addition, the weaning transition is an essential phase for the manipulation of rumen development using nutritional strategies, which can affect ruminant growth performance and health (Sun et al, 2021). The current study results confirmed the beneficial effects of solid feed to enhance the preweaning growth and overcome the weaning stress.…”
Section: Body Weight and Carcass Weightsupporting
confidence: 78%
“…Moreover, Cui et al (2020) showed the increased rumen papillae height and width, and muscle layer thickness of rumen by starter intake. The rumen epithelial thickness and rumen papillary were improved in solid feed (Sun et al, 2021).…”
Section: Rumen Histomorphologymentioning
confidence: 97%
See 2 more Smart Citations
“…In this progress, PPAR α promoted papillary development by activating HMGCS2 ( Connor et al, 2013 ). ACAT1 , BDH1 , HMGCL , and HMGCS2 were found involved in the pathways of synthesis and degradation of ketone bodies and butanoate metabolism, which were found as features of rumen wall development ( Sun et al, 2021 ). Microbial fermentation of dietary carbohydrates in the rumen produces large amount of short-chain fatty acids (SCFAs) ( Poulsen et al, 2012 ), such as butyrate, which are known to affect rumen development and stimulate rumen epithelial cells proliferation in vivo ( Sakata and Tamate 1978 ).…”
Section: Discussionmentioning
confidence: 99%